Controls on nitrate‐N concentrations in groundwater in a Missourian claypan watershed. Issue 3 (6th March 2016) - Al‐Qudah, Omar M.; Liu, Fengjing; Lerch, Robert N.; Kitchen, Newell; Yang, John
Abstract: Nitrogen (N) fertilizer applications have resulted in widespread groundwater nitrate‐N (NO3 ‐N) contamination in the U.S. Corn Belt. Goodwater Creek Experimental Watershed (GCEW) is an agricultural watershed in the claypan soil region of northeastern Missouri with a network of 96 wells at depths of 2.7–15.7 m. The objectives of this study were to (1) inspect the spatial and temporal variations of NO3 ‐N concentrations in GCEW's groundwater, particularly with well depth at scales ranging from individual well, well nest, and field to the entire watershed during the period 1991 to 2004; (2) understand the processes controlling the variability of NO3 ‐N concentrations in groundwater at various scales within GCEW; and (3) compare groundwater NO3 ‐N concentrations in GCEW to other agricultural watersheds in the U.S. Nitrate‐N concentrations were determined in more than 2000 samples collected from 1991 to 2004. Despite the low hydraulic conductivity of the claypan soils, considerable NO3 ‐N contamination of the glacial till aquifer occurred, with 38% of the wells exceeding 10 mg L −1 . Groundwater recharge by preferential pathways through the claypan appeared to be the primary mechanism for NO3 ‐N movement to the aquifer. Changes in concentration with depth steadily increased to 8.5–10 m and then decreased with further depth. This pattern was consistent with decreased hydraulic conductivity in the Paleosol layer at 8.5–10 m, denitrification below this layer, and mixing of recent contaminated water with older uncontaminated water in the lowest strata. Only 19–23% of sampled wells exceeded 10 mg L −1 in nonclaypan agricultural watersheds over the continental U.S., suggesting that groundwater in GCEW was more susceptible to NO3 ‐N contamination than nonclaypan watersheds. These results demonstrated that preferential flow through the soil and hydraulic conductivity of the subsurface strata controlled NO3 ‐N transport in this claypan watershed. Key Points: Groundwater in claypan watersheds was more susceptible to NO3 ‐N contamination Preferential pathways were the primary mechanism for NO3 ‐N movement to groundwater Hydraulic conductivity controlled NO3 ‐N distributions over strata in the aquifer